The Effect of Marketing Mix and Brand Image towards Interest of Students at Riyadlul Jannah Islamic High School Jonggol - Aziz, Thoriq; Noorman Haryadi, Rofiq; Riyanto, Sugeng; HM, Usman (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
The purpose of this study was to find out whether Marketing Mix and brand image have a significant effect on the Choice Decision students at Riyadlul Jannah Jonggol Islamic High School. The approach used is quantitative with data collection techniques or questionnaires, int erviews, observation, and documentation. The population in this study were madrasa heads, teachers, employees, and parents of students. Sampling amounted to 50 people from 168 people in the population using the slovin formula with probability random sampling. Data were analyzed using the classical assumption test and hypothesis testing with the help of the SPSS Version 22 program. The results showed that: (1) The Marketing Mix variable had a significant effect on the Choice Decision students at Riyadlul Jannah Jonggol Islamic High School by 54% with a significance value - 0.000 less than the value of α = 0.05 and the calculated t value of 1,598 is greater than the t table value of 0,278. (2) The brand image variable has a significant effect on the Choice Decision students at Riyadlul Jannah Jonggol Islamic High School by 42% with a significance value = 0.000 less than the value of α = 0.05 and a t-count value of 1,128 greater than t-table 0,278. (3) Simultaneously, Marketing Mix and brand image have a significant effect on the Choice Decision students at Riyadlul Jannah Jonggol Islamic High School by 64.9% with a significance value of 0.000 which is less than 0.05 and the calculated F value obtained is 43.376 greater than the value F table 2.90